(Mathematical Induction and Binomial Theorem) : Like Our Page For Entry Test Material & Admission Updates

Download as pdf or txt
Download as pdf or txt
You are on page 1of 10

 Like our page for entry Test Material & Admission Updates

www.facebook.com/ecat.netprep/
CHAPTER 8
(Mathematical Induction
and Binomial Theorem)
Look Exercise 8.1. The Questions are like this:

1. 1+5+9+….+(4n-3) = n(2n-1)
2. 1+3+5+….+(2n-1) = n² and so on..

-TRICK:-
On the right side of equality, the formulas of Sum of series are given
and to the left side of equality nth term/General Term of series is given.
In Question 1, nth term is (4n-3) and formula for sum of series is n(2n-
1). an= (4n-3)
Sn = n(2n-1)
Given is a1=1, a2=5 and a3=9.
Now if you put n= 1,2 and 3 in an you will get 1,5 and 9 respectively.
a1=[4(1)-3]=1
a2=[4(2)-3]=5
a3=[4(3)-3]=9
If you put n=1 in Sn, you will get the first term as it is. S1=a1
S1= 1[2(1)-1]= 1
If you put n=2 in Sn, you will get the sum of first two terms of series.
S2=a1+a2
S2= 2[2(2)-1]= 6
If you put n=3 in Sn, you will get the sum of first three terms of the
series. S3= a1+a2+a3
S3= 3{2(3)-1] = 15

©All copyrights reserved to “Ecat/Net Aspirants”


 Like our page for entry Test Material & Admission Updates
www.facebook.com/ecat.netprep/
I hope this is clear to you. Now in MCQ’s, they will give you left side of
the question and you have to guess the right side from the options.
Example:-
1x3+2x5+3x7+…..+nx(2n+1)= ?
( )( ) ( )( )
a) b) c)____ d)_____
Now to guess which is the right option, do following steps:

Calculate S1, S2 and S3 by S1=a1 , S2=a1+a2 , S3= a1+a2+a3


S1=3, S2= 13 , S3= 34
Now put n=1, 2 and 3 in all the given options and check for which
option your answers matches with S1, S2 and S3 you first calculated. It
will be the answer. In above question option b is correct. Check
minimum 3 values by putting n. Practice it maximum.
-Binomial Expression:-
An algebraic expression consisting of only two terms is called a binomial
expression.
For Example:
(x + y)2= x2+2xy+y2=2C0x2+2C1xy+2C2y2
Binomial Theorem:-
This theorem gives a formula by which any power of a binomial
expression can be expanded. It was first given by Sir Isaac Newton.
Important Points:-
1) There must be two terms or made them two.
e.g. a+b or (a+b+c) (a+(b+c))
2) Power must be positive integer. e.g. Z={0,1,2,3,….}
3) Last term of binomial theorem exists.
4) Total number of terms of binomial expansion is always one more
than index. i.e. n+1
e.g.  No. of terms in (x+y)2 is 2+1

©All copyrights reserved to “Ecat/Net Aspirants”


 Like our page for entry Test Material & Admission Updates
www.facebook.com/ecat.netprep/
Easy Way to learn this theorem:-
Words:- Power or a wali term ko mila k power pehly, a wali term ki
power me se aek km or b wali term ki power me izafa krna hae, Mtlb ye
k pehli 2 laqmo ko km krna hae or tisri ko brhana hae. Or Last pe, pehli
term se 0! , Second pe 1! And so on. Divide krna hae…
In general:-
( )
(a+b)n= + + + ⋯+
! ! ! !
Illustration:-
Let us have an example:-
( ) ( )( )
(x+y)2= + + = +2 + (Answer)
! ! !
Even Binomial Coefficient:-
If r=0,2,4,6,8…. then nCr is called even places or even binomial
coefficient.
Odd Binomial Coefficient:-
If r=1, 3, 5, 7, 9… then nCr is called odd places or odd binomial
coefficient.
Sum of Binomial Coefficients:-
n
C0+nC1+nC2+…+nCn=2n
Example:- Find the Sum of binomial Coefficient in the binomial
expansion of (x+y)5?
Solution:- Sum of Binomial Coefficient= 25=32 (Answer)
Sum of Even Binomial Coefficients is equal to sum of odd binomial
Coefficient.
n
C0+nC2+nC4+…+nCn= nC1+nC3+nC5+…+nCn-1=2n-1
Example:- Find the sum of Even Binomial Coefficients of (2x+3y)6 ?
Solution:- Sum of Even Binomial Coefficients=26-1=25=32(Answer)
Sum of all exponents in (x+y)n= n2+n

©All copyrights reserved to “Ecat/Net Aspirants”


 Like our page for entry Test Material & Admission Updates
www.facebook.com/ecat.netprep/
Examples:- Find the sum of all exponents of (a+x)3?
Solution:- Sum of all exponents=32+3=12 (Answer)
 The binomial coefficient of the term equidistant from the beginning
and the end are equal i.e nCr=nCn-r
 General term/Specific Term of (a+b)n: Tr+1=nCr an-r.br
a) Tr+1 is the (r+1)th term from beginning and (n-r+1)th term from end.
b) Value of r is one less than number of term
c) nCr is the binomial coefficient of (r+1)th term.
 rth term of (a+b)n : Tr=nCr-1.an-r+1.br-1
 nth term of (a+b)n: Tn=nCn-1.abn-1
 Last term/(n+1)th term of (a+b)n:Tn+1=bn
Middle term/s
a) The middle term in the binomial expansion of (a+b)n depends upon
the value of n
b) If n is even then there is only one middle term. i.e +1

c) If n is odd then there are two middle terms i.e ( )


 Coefficient of Middle terms:
a) If n is even then binomial Coefficient of middle term is nCn/2
b) If n is odd then binomial Coefficient of middle terms are nC(n-1)/2 or
n
C(n+1)/2
 pth term from the end in the Binomial Expansion of (a+b)n is
(n-p+1)th term from the beginning.
Properties of nCr
1) If n is even then greatest coefficient= nCn/2
2) If n is odd then greatest coefficient=nC(n-1)/2 or nC(n+1)/2
3) If 0<r<n , n,rԑN, then nCr=n/r.n-1Cr-1
4) nCr+nCr-1=n+1Cr

©All copyrights reserved to “Ecat/Net Aspirants”


 Like our page for entry Test Material & Admission Updates
www.facebook.com/ecat.netprep/
n n
5) Cx= Cy x=y or x+y=n
6) If l,m are integers then sum of coefficients in the expansion of
(lx+my)n is (l+m)n

CONVERGENCE OF BINOMIAL SERIES:-


 Binomial Series is valid if it is convergent.
 In convergent series, next term is smaller i.e we can neglect bigger
terms of order x4, x5,…….

Condition:-
 Binomial series converges if,
|x|<1 or -1<x<1 or x Є(-1,1)

Examples:-
1. (1+3x)-7 , Series is convergent if x=?
Applying condition,
|3x|< 1  |x|<
2. (1- x)1/2 , Series is convergent if x=?
Neglect –ve sign
| x| < 1  |x|<
3. (3+4x)-2
In this case, first take out 3 common and then check
3-2(1+ x)-2 Now, | x|< 1  |x|<
Some particular cases of expansion (1+x)n when n<0

Binomial Expansion (r+1)th term


(1+x)-1 (-1)rxr

©All copyrights reserved to “Ecat/Net Aspirants”


 Like our page for entry Test Material & Admission Updates
www.facebook.com/ecat.netprep/
-2
(1+x) (-1)r(r+1)xr
(1+x)-3 ( )( ) r
(-1)r x
(1-x)-1 xr
(1-x)-2 (r+1)xr
(1-x)-3 ( )( ) r
x

-Entry Test Type MCQ:-


Q#1: The number of terms of (a-b)17 is:
A) 2 B) 17 C) 18 (Correct) D) 20
Solution: The total terms in binomial expansion is n+1
In this case: n=17 so Total terms =17+1=18 (Answer)
Q#2: The middle term in the expansion of (x+y)30 is:
A) 13th B) 14th C) 15th D) 16th (Correct)
Solution: As we know that n=30
so middle term will be ( +1)th  =( +1)th =16th (Answer)
Q#3: The binomial coefficient of 21st term in the expansion of (a+b)23 is:
A) 1771 (Correct) B) 2891 C) 3421 D) 1563
Solution: As 21st term is asked so r=20
Using the general term formula:
Tr+1= nCr. an-r.br
T20+1= 23C20 . a23-20b20
T21= 23!/20!. 3! a3b20
T21= 23.22.21/6 a3b20
T21= 23.11.7 a3b20
T21= 1771 a3b20 (Answer)
Q#4: The total number of terms in the expansion of (1-x+x4)4 is:
A) 5 B) 15 (Correct) C)10 D) 8

©All copyrights reserved to “Ecat/Net Aspirants”


 Like our page for entry Test Material & Admission Updates
www.facebook.com/ecat.netprep/
Solution: As we know that:
Total number of terms in (x1+x2+…..+xr)n is n+r-1Cr-1
whereas r= no. of terms
( )( )
And also for trinomial expansion total terms is
In this case:
M#1: (1-x+x4)4
As r=3 so Total number of terms 4+3-1C3-1= 6C2=15 (Answer)
( )( ) ( )
M#2: Number of terms in trinomial expansion= = =15 (Ans)

Q#5: The coefficient of the term involving x5 in the expansion of


− ? A) 15309 B) -15309 C) -15309/8(Correct) D) 15309/8

Explanation:
Trick:
The coefficient of the term involving xm in the expansion of
(xp+(a/xq))n is Tr+1=nCr an-r.br whereas r=
( )
Apply the trick: r= = =5
So T5+1= 10C5 (x2)10-5.(-3/x2)5= -15309/8 (Answer)

Q#6: The term free from Z in the expansion of + is:

A) 5/4 B) ¼ C) 9/4 D) 4/5


Explanation:
Trick:
The coefficient of the term involving xm in the expansion of (xp+(a/xq))n
is Tr+1=nCr an-r.br whereas r=

©All copyrights reserved to “Ecat/Net Aspirants”


 Like our page for entry Test Material & Admission Updates
www.facebook.com/ecat.netprep/
Here in this case m=0 as independent term/term free from
variable/constant term contain x0 always so that:
( )
r= = =2
/
T2+1= 10C2 (z/3)4.(3/2z2)2 =5/4 (Answer)

Q#7: The term free from t in (4t+5/t)8 is?


Explanation:
Using trick: r= np/p+q r= 1(8)/1+1 4
so Tr+1= T5  5th term (Answer)
Q#8: Total number of terms in the expansion of (x+z)50+(x-z)50 are?
Explanation:
Trick: Total terms of (x+y)n+(x-y)n are:
1) If n=odd then total terms are (n+1)/2
2) If n=even then total terms are (n/2)+1
In this case: (50/2)+1= 26 (Answer)
Q#9:The coefficient of x5 in the expansion of (1+x2) (1+x)4 is?
Explanation:
Using binomial theorem on (1+x)4
=(1+x2)(1+4x+6x2+4x3+x4)
=1+4x+7x2+8x3+4x5+x6
So coefficient of x5 is 4 (Answer)
Q#10:
The coefficient of terms x100 in the expansion of (1-x)-3 is?
Explanation:
Using the formulas:
( )( ) ( )( )
(r+1)th term of (1-x)-3 is  = 5151

©All copyrights reserved to “Ecat/Net Aspirants”


 Like our page for entry Test Material & Admission Updates
www.facebook.com/ecat.netprep/
Q#11:
If the coefficient of (2r+4)th and (r-2)th term in the expansion of (1+x)18
are equal?
Explanation:
Using the property”
nCx=nCy  n=x+y
so: 2r-3+r-3=183r=18r=6 (Answer)
Q#12:The sum of coefficient of last 3 last term in the expansion of
(8-3x)1/2?
Explanation: The last term of the binomial series does not exist so can’t
be determined.
Q#13: If the coefficient of x2 and x3 in the expansion of (3+ax)9 are same
then a=?
Explanation:
Using the formula:
Tr+1= nCr. an-rbr
Tr+1= 9Cr (3)9-r(ax)r
For x2 T3= 78732(ax)2
For x3 T4=61236(ax)3
As the coefficient are equal so that:
78732(ax)2=61236(ax)3
 a= 9/7 (Answer)
Q#14:The greatest positive integer divides 11n-10n-1 is?
Explanation:
Put n=1 it gives the notation n=0
Put n=2 it gives the 112-10(2)-1= 121-20-1=121-21=100
which means greatest integer is 100.. (Answer)
Q#15:

©All copyrights reserved to “Ecat/Net Aspirants”


 Like our page for entry Test Material & Admission Updates
www.facebook.com/ecat.netprep/
2
If S(n)= n -n+41 is a proposition then which of the following is not prime
A) S(1) B) S(1) and S(10) C) S(10) D) S(41)
Explanation:
On putting the value of n from the given options and satisfies the
condition.
so option D is satisfying.
S(41)= (41)2-(41)(41)
S(41)=412=1681
As we know that prime number is one which has at most 2 divisor i.e
itself and 1.
In this case there are three divisor of 1681 i.e 1681 ,41 and 1 (Answer)
Q#16:
If a3+b3+c3+….+(2n-1)3=n2(2n2-1) then value of (a,b,c)=?
Explanation:
Put n=1 in both (2n-1)3 and n2(2n2-1) and get the answer.
As in this case (2(1)-1)3=1 so n2(2n2-1) is also 1
Put n=2 in both notation so:
(2(2)-1)3=27 so n2(2n2-1)=1+27=28
Put n=3 in both notation so:
(2(3)-1)3=125 so n2(2n2-1)=1+27+125=153
so (1,27,125)= (a3,b3,c3)
taking cube root on both sides so:
(1,3,5)=(a,b,c) (Answer)

©All copyrights reserved to “Ecat/Net Aspirants”

You might also like

pFad - Phonifier reborn

Pfad - The Proxy pFad of © 2024 Garber Painting. All rights reserved.

Note: This service is not intended for secure transactions such as banking, social media, email, or purchasing. Use at your own risk. We assume no liability whatsoever for broken pages.


Alternative Proxies:

Alternative Proxy

pFad Proxy

pFad v3 Proxy

pFad v4 Proxy